At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Our platform offers a seamless experience for finding reliable answers from a network of experienced professionals. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

If x ¤ y = (x + y)² - (x - y)²
Then √5 ¤ √5 =


Sagot :

[tex]x\ \diamond\ y=(x+y)^2-(x-y)^2=x^2+2xy+y^2-(x^2-2xy+y^2)\\\\=x^2+2xy+y^2-x^2+2xy-y^2=4xy\\\\\sqrt5\ \diamond\ \sqrt5=4\cdot\sqrt5\cdot\sqrt5=4\cdot5=20[/tex]